Allium Cepa (Onion) Extract Enhances and Protects Testicular Function and Architecture against Paraquat Induced Oxidative Damage. - Uzozie Chikere, Ofoego; Ejike, Daniel Eze (International Journal of Life science and Pharma Research, 2021)
Allium cepa (A. cepa) is consumed for its health benefits. This study investigated the therapeutic potentials of ethanolic extract of A. cepa bulbs against paraquat-induced testicular toxicity in animal model. Thirty Wistar rats were split into control and five test groups (n=5). Group A (Control) received feed and water; test groups (B-F) were treated orally as follows: group B (20 mg/kg b.w. of paraquat for 4weeks); group C (1000 mg/kg b.w. of A. cepa extract for 4weeks); group D (a co-administration of 20 mg/kg b.w. of paraquat and 100 mg/kg b.w. of A. cepa extract for 4weeks); group E (a co-administration of 20 mg/kg b.w. of paraquat and 1000 mg/kg b.w. of A. cepa extract for 4weeks); and group F (1000 mg/kg b.w. of A. cepa extract for 2weeks before co-administration with 20 mg/kg b.w. of paraquat for 2weeks). In the end, sperm count, morphology, motility, sera testosterone levels, malondialdehyde (MDA) and superoxide dismutase (SOD) levels as well as histology of the testes were assessed. Paraquat administration caused significantly (P<0.05) reduced sperm count, motility, alteration in sperm morphology and induced cell death. Oral gavage of paraquat also caused significant (P<0.05) decrease in serum testosterone and SOD levels with concomitantly elevated MDA levels. However, following the co-administration with ethanolic extract of A. cepa to experimental rats, there was an improvement in sperm parameters (count, motility and morphology) as well as in sera testosterone and SOD levels. It can be concluded that A. cepa exerts strong antioxidant effects in a dose-dependent manner in ameliorating testicular toxicity induced by paraquat in animal models.